2022
DOI: 10.1016/j.drugalcdep.2022.109267
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression symptom level with smoking urges, cigarette withdrawal, and smoking reinstatement: A preliminary laboratory study

Abstract: Background: Cigarette smoking urges, withdrawal, and smoking reinstatement may be especially relevant to people with elevated depression symptoms who smoke. This laboratory study aimed to assess relations between depression symptom level and smoking urges for reward and relief, cigarette withdrawal, and smoking reinstatement in people who smoke cigarettes daily during acute abstinence and while smoking as usual. Methods: Participants with low (n=51) or elevated (n=29) baseline depression symptoms underwent two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Third, withdrawal symptom scores during experimental sessions were relatively low (i.e., average of 1.26 on a scale of 0-5), suggesting either a floor effect on this measure or that participants (especially those with relatively low levels of nicotine dependence) may not have experienced symptoms severe enough to benefit from pharmacological intervention. While our results indicate that 12-hr abstinence produced significant increases in withdrawal symptoms compared to baseline nonabstinent levels (indicating that experimental session values were greater than a potential floor effect), and previous studies have shown similar ranges of withdrawal symptoms during 12-to 16-hr abstinence (Hendricks & Leventhal, 2013;Leventhal et al, 2010;Tucker et al, 2022), future studies may investigate oxytocin-related effects during longer term abstinence and among a population of individuals with relatively high nicotine dependence. Finally, while a strength of the present study-compared to previous studies-is the testing of two active dose levels of oxytocin, this limited dose range likely makes it difficult to ascertain the dose-response curve of oxytocin on subjective experiences of nicotine abstinence.…”
Section: Discussioncontrasting
confidence: 43%
“…Third, withdrawal symptom scores during experimental sessions were relatively low (i.e., average of 1.26 on a scale of 0-5), suggesting either a floor effect on this measure or that participants (especially those with relatively low levels of nicotine dependence) may not have experienced symptoms severe enough to benefit from pharmacological intervention. While our results indicate that 12-hr abstinence produced significant increases in withdrawal symptoms compared to baseline nonabstinent levels (indicating that experimental session values were greater than a potential floor effect), and previous studies have shown similar ranges of withdrawal symptoms during 12-to 16-hr abstinence (Hendricks & Leventhal, 2013;Leventhal et al, 2010;Tucker et al, 2022), future studies may investigate oxytocin-related effects during longer term abstinence and among a population of individuals with relatively high nicotine dependence. Finally, while a strength of the present study-compared to previous studies-is the testing of two active dose levels of oxytocin, this limited dose range likely makes it difficult to ascertain the dose-response curve of oxytocin on subjective experiences of nicotine abstinence.…”
Section: Discussioncontrasting
confidence: 43%
“…Items are summed to determine a total score ranging from 0 to 60. As in our prior work (Pang, Tucker, D'Orazio, Weinberger, & Guillot, 2022;Tucker, et al, 2022), a binary CESD score was created for elevated depression symptoms (≥20) and low depression symptoms (<20). A meta-analysis in general populations and primary care settings found a cutoff of 20 showed better sensitivity to specificity trade-off than the generally recommended cutoff of 16 (Vilagut, Forero, Barbaglia, & Alonso, 2016).…”
Section: The Center For Epidemiologic Studies Depression Scale (Ces-d)mentioning
confidence: 99%
“…People with depression are at higher risk of becoming smokers, and smoking seems to be associated with later depression (Fluharty et al, 2017;Sánchez-Villegas et al, 2021). Also, smokers with depression encounter more significant barriers to smoking cessation than those without depression (Ranjit et al, 2020) and show higher levels of nicotine dependence (Bainter et al, 2020), stronger urges to smoke when anticipating the relief from a negative mood state (Berlin & Singleton, 2008), higher relapse rates (Huffman et al, 2018;Zvolensky et al, 2015) and a more intense withdrawal syndrome when compared to smokers with lower levels of depressive symptomatology (Tucker et al, 2022).…”
mentioning
confidence: 99%